Enacting history - Hirsch, Mira, author.
1 online resource
Keywords: "Enacting History is a practical guide for educators that provides methodologies and resources for teaching the Holocaust through a variety of theatrical means, including scripted texts, verbatim testimony, devised theater techniques, and process-oriented creative exercises. A close collaboration with the USC Shoah Foundation I Witness program and the National Jewish Theater Foundation Holocaust Theater International Initiative at the University of Miami resulted in the ground-breaking work within this volume. The material facilitates teaching the Holocaust in a way that directly connects students to individual people and historical events through the art of theater. Each section is designed to help middle and high school educators meet curricular goals, objectives and standards and to integrate other educational disciplines based upon best practices. Students will gain both intellectual and emotional understanding by speaking the words of survivors, as well as young characters in scripted scenes, and developing their own performances based on historical primary sources. This book is an innovative and invaluable resource for teachers and students of the Holocaust; it is an exemplary account of how the power of theatre can be harnessed within the classroom setting to encourage a deeper understanding of this defining event in history"--Provided by publisher.